Vector potential of the brown – banded cockroach Supella longipalpa (F.) (Dictyoptera – Epilampridae) for bacteria Psedomonas aeruginosa (Journal of the College of Basic Education, 2022)
This research shows that the brown – banded Cockroach can transmit pathogenic bacteria Psedomonas aeruginosa in laboratory. The brown – banded cockroach Supella longipalpa (F.) was an effective mechanical transmitter of bacteria via feces. Groups of restrained brown – banded cockroaches from a laboratory colony free of Psedomonas sp. were fed graded doses of Psedomonas aeruginosa and their feces were assayed daily. The amount and duration of Psedomonas in feces is dose related with output from 1.1 × 10 to 6.4 × 104 cell / ml over a range of 3 - 20 days. The percentage of specimens excreting Psedomonas aeruginosa is also dose related and ranges from 40% with a 102 to 80% with a 106. There were no significant sex differences in excretion of Psedomonas at each dose.